Potencjał intelektualny w kontekście intraregionalnej polityki innowacyjnej - Golińska-Pieszyńska, Małgorzata (Intellectual Potential in the Context of Intraregional Innovative Politics, 2008)
Currently Poland is pointing towards creating an economical system based on the knowledge, whose development is dependant on economy's ability to create new knowledge and to take full advantage of already possesed knowledge. In discussions concerning the management of knowledge we can often come across terms like "intellectual capital" and "management of intellectual capital". The question of intellectual capital is relatively compound. The article is an attempt to grasp the relations between intellectual potential and innovative politics which is now the subjects of many interdisciplinary considerations. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 103-112